Faktor Determinan Motivasi dan Hasil Belajar Matematika Siswa SMP Negeri 1 Surakarta - Irmawanti, Nur; Sutama, S (Universitas Muhammadiyah Surakarta, 2018)
The purpose of the study is to assess the influence of student activeness, learning facilities, and socio-economic level of parents to the result of learning mathematics indirectly through student’s learning motivation. The type of the research is quantitative with research population 266 student of class VII of SMP Negeri 1Surakarta. The sample of 160 students was calculated by Slovin formula. The technique of collecting data used are questionnaires and documentation. Sampling using proportional random sampling method. The technique of analizing data is path analiysis. As the result of the research, Student Activity, Learning Facility, socio-economic level of parents simultaneously contributes to the Mathematics Learning Outcomes through Motivation Learning with (